Democracy in the Shadow of Identity: A Comparative Study of the 2019 General Elections in Indonesia and India - Bareto, Aldi; Fahrezhi, Farel Al; Dafriansyah, Muhammad Andryan; Alfaridzy, Muhammad Keanu; Saputra, Rehan (Journal of Political Sphere, 2025)
In contemporary democracies, elections are not merely contests of policy and vision but increasingly arenas where identity politics shape voter behavior. This paper examines how collective identities particularly religion became central instruments in the 2019 general elections of Indonesia and India, two populous and multicultural democracies. Using a qualitative-descriptive approach with a comparative case study design, this research analyzes how political actors mobilized identity-based narratives to influence electoral outcomes. Data were collected from academic literature, political documents, speeches, media reports, and digital campaign materials. In India, the Bharatiya Janata Party (BJP) effectively utilized Hindu nationalism as a campaign tool, supported by digital platforms, to consolidate the Hindu majority vote. In Indonesia, Islamic identity narratives played a significant role in shaping support for the presidential candidates, with religious figures actively participating in identity-based mobilization. The findings suggest that identity politics in both countries contributed to social polarization, undermining democratic deliberation and national integration. This study offers a critical reflection on the consequences of identity-driven politics in democratic societies.